Discovering adult education at McGill University and the University of British Columbia - MacLean, Scott (Canadian Journal for the Study of Adult Education, 2009)
In the early 1920s, McGill University and the University of British Columbia (UBC) were engaged in a traditional form of university extension: the deliveryof evening lectures by university faculty members to people not enrolled as undergraduate or graduate students. By 1935, each university had discovered the broader terrain of adult education and declared itself to be a provider of a range of educational programs and services for working adults. At McGill, adult education was established as an institutional priority in 1928 and largely disappeared by the early 1940s. At UBC, adult education was discovered in 1935 and was sustained as a prominent institutional priority until the 1960s. This article narrates the discovery and establishment of adult education at two of Canada’s most prestigious universities, and explores what this narrative means for ourunderstanding of the role of universities in Canadian adult education. Résumé Tôt dans les années 1920s, McGill University et l’University of British Columbias’engageaient dans une forme traditionnelle de l’extension universitaire : les conférences de soir données par les membres de faculté aux gens qui ne furent pas inscrits comme étudiants réguliers. Avant 1935, chaque université a découvert le terrain plus divers de l’éducation des adultes, et s’est déclaré fournisseur d’une gamme des programmes et services éducatives pour les adultes. À McGill, l’éducation des adultes a été établie comme priorité institutionnelle en 1928, mais cette priorité a plus ou moins disparu à partir des années 1940s. À UBC, l’éducation des adultes a été découvert en 1935, et a été soutenue comme priorité institutionnelle jusqu’aux années 1960s. Cette article raconte la découverte et l’établissement de l’éducation des adultes à deux des plus prestigieux universités Canadiens, et explore ce que cet narratif veut dire pour notre compréhension durôle des universités dans l’éducation des adultes au Canada.